Estudo de eficiência em linha de produção de sistemas de descarga de granéis através da simulação computacional - Soffiatti, Evandro Carlos (2016)
The study represents the development of a computational model, applied to the study of efficiency in work equipment manufacturing process stations, used for lifting and tipping trucks in grain landfill, in a company located in the South Region of Brazil. The project presents the layout of the production line and the current stage of the process and is exploring possibilities for solutions to the problems of disorientation adhesion between the jobs and the low efficiency in production, and the ability results in improvement of productivity. Developed a computational model to simulate where simulations are performed using hypothetical alternative scenarios, in order to obtain solutions to the listed problems. Obtained good results in terms of production processes, the alignment efficiency and better adhesion between the jobs, which have an average increase of 26% when modeling the line in its entirety, with increases of approximately 2.5 % in the production of sub assemblies appointed by the beam profile. There is also reduction in production time cycle, which yields 2.5% improvement, value that justifies the increased productivity that matches the approximate annual earnings of R$ 362,000.00. Complementing the financial results, there is an annual reduction of approximately R$ 33.000.00 in costs of labor allocated to the process, representing opportunities for improvement in service to internal and external customer, as well as organization and sequencing of the production line.